Wartenberg Syndrome - an Unusual Neuropathy - Case Report and Literature Review - MIHAI MEHEDINTU-IONESCU; OVIDIU STEFANESCU; RADU CRISTIAN JECAN (Modern Medicine)
Almost known in the literature and underdiagnosed even in the obvious cases, Wartenberg syndrome is most often treated, superfi cially and as a result, with direct consequences on its evolution. These elements ultimately lead to loss of cases and reporting in the literature as a rarity or other condition of the radial nerve, superfi cial branch. It must be understood at first that the radial nerve is susceptible to compression in different ways along the anatomical path. Causes are all common in the upper limb, compression and trauma. The two elements (compression and trauma) affect the superficial branch of the radial nerve at the time of its passage between the brachioradial muscle and the supinator muscle, as a result the patients complain of ‘’hand pain‘’. They describe only sensitive disorders but not motor disorders. The pain is described distally by the radial foramen and is accompanied by paresthesia on the dorsal side of the hand. The present case shows a female person working in a car parts factory where they have to pick up considerable parts to inspect them. The pieces are positioned on different side, as a result he must use the muscles of the forearm to turn them.